Minimization of transportation risks in logistics by choosing a cargo delivery route with the minimal projected number of road accidents - Oklander, Mykhailo; Yashkina, Oksana; Yashkin, Dmytro (Eastern-European Journal of Enterprise Technologies, 2019)
A scientific-methodological approach to selecting a route with a minimal projected number of road accidents among several possible routes that connect the points of departure and destination has been proposed, which is based on three steps: the first step implies building a directed graph that contains the points of departure, delivery, as well as intermediate points, which are linked by edges with the specified distances between the points; the second step implies the calculation of the projected number of road accidents for each edge as the product of the distance that a truck must travel over a specific region by a road accident indicator, which is calculated for a given region; at the third step, a route is determined with the minimal projected number of road accidents. A decision maker can be guided by two strategies: a first strategy is to choose the shortest delivery path – this would minimize the cost of delivery; a second strategy is to choose a route with the minimal projected number of road accidents ‒ this minimizes accidents indicators. The current study has stated the problem of multifactor optimization based on distance and the projected number of road accidents and has proposed a Pareto-optimal solution. The proposed method could prove useful for operations by transportation and logistics enterprises when substantiating the safest routes to deliver cargoes, taking into consideration the importance of minimizing the cost of delivery. The software for interactive maps and navigation systems includes widely known methods for determining the shortest distance, a route that takes minimum time, or a route that avoids "traffic jams". It has been proposed to consider adding the algorithm, which was developed based on the proposed method for choosing a route with the minimal projected number of road accidents, as one of the alternatives to choose the optimal route